Optimalisasi Psikologi Perkembangan Anak dalam Lingkungan Keluarga - Manbaul Hikam, Hilmi; Usriyah, Lailatul; Mualimin, Mualimin (Mulya Literasi Publishing, 2025)
The psychology of child development is one of the most common problems, especially in the family environment. Difficulty in educating because it is not by expectations prevents children not growing or developing according to their age. This article uses a type of library research. This research was conducted to collect and analyse data from books, magazines, newspapers, and other works. Library research uses a qualitative approach. Based on the results of various studies presented to discuss the problem currently faced, not all family environments can meet the hopes and needs of children, especially in their developmental psychology. A family environment that acts as a good educator and meets standards becomes a necessity for parents. If not, then the child's developmental psychology is at stake, because parents and children work together to support their future. Family environment, especially parents, is the first education for child development psychology. The process of child development in various aspects, such as language, physical-motor, and emotional, must receive important support in the family environment because it can be used as capital in children's lives in the future.